Development of Halal Tourism Based on Islamic Values in Kampung Kang Bejo, Balikpapan - Dwi Ratna Sari; Bambang Iswanto; Darmawati Darmawati (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the potential, challenges, and strategies for developing halal tourism in Kampung Wisata Kang Bejo, Balikpapan. Halal tourism has become one of the strategic sectors in the tourism industry due to the increasing demand for Muslim-friendly tourism destinations. Kampung Wisata Kang Bejo possesses considerable potential through its community-based tourism concept, local cultural attractions, environmental education, and the availability of natural tourism resources that can support the implementation of halal tourism. However, several challenges remain, including limited halal facilities, lack of public understanding regarding halal tourism concepts, inadequate infrastructure, and minimal promotional activities. This research employed a qualitative descriptive approach through observation, interviews, and documentation techniques. Data were analyzed using data reduction, data display, and conclusion drawing methods. The findings indicate that the development of halal tourism in Kampung Wisata Kang Bejo requires synergy between the community, tourism managers, and the government. Development strategies can be implemented through improving halal facilities, strengthening human resources, utilizing digital promotion, and optimizing community participation based on the principles of Community Based Tourism (CBT). The study concludes that Kampung Wisata Kang Bejo has strong potential to become a halal tourism destination in Balikpapan if supported by sustainable management and stakeholder collaboration.